2020
DOI: 10.6007/ijarafms/v10-i1/7009
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of HRM Practices in Organizational Justice on Innovative Work Behavior among the Hotel Industry of Pakistan

Abstract: Justice is an important element in any organization. Innovative work behavior and Human ResourceManagement practices (HRMPs) are affected by organizational justice (Distributive, Procedural, Interpersonal & informational). For this paper distributive justice is selected as an independent variable. The purpose of this paper is to explore the mediating effect of HRM practices in organizational justice on innovative work behavior among the hotel industry of Pakistan. In total, 151 personnel were selected from 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…In mediation scenario (HRMP) are positively mediating between distributive justice and innovative work behavior of employees. Flint and Haley (2013), Ghosh, Sekiguchi, and Gurunathan (2017) Ismail (2019; Leelamanothum, Na-Nan, andNgudgratoke (2018), andMaslach, Schaufeli, andLeiter (2001) supported the current study. The distributive justice, innovative work behavior and human resource management practice should be the most integral part of the organization.…”
Section: Discussion and Implementationsupporting
confidence: 60%
See 1 more Smart Citation
“…In mediation scenario (HRMP) are positively mediating between distributive justice and innovative work behavior of employees. Flint and Haley (2013), Ghosh, Sekiguchi, and Gurunathan (2017) Ismail (2019; Leelamanothum, Na-Nan, andNgudgratoke (2018), andMaslach, Schaufeli, andLeiter (2001) supported the current study. The distributive justice, innovative work behavior and human resource management practice should be the most integral part of the organization.…”
Section: Discussion and Implementationsupporting
confidence: 60%
“…The outcome of the current study is different from the previously conducted studies in the same field. But there are also some previous studies conducted on the impact of organizational justice and employee positive behavior that include the study conducted by Gozukara et al (2016), Ismail (2019), indicated a negative relationship between distributive justice and innovative work behavior.…”
Section: Discussion and Implementationmentioning
confidence: 99%
“…So There are many research study the relationship between ethical behavior of employees and organizational justice. Therefore, in this research, the researcher analyzes previous studies that dealt with the relationship between organizational justice and its relationship to bullying behavior in the workplace, By presenting the previous studies for each of the research variables, and the studies that dealt with the relationship between organizational justice and bullying in the workplace, Finally the researcher concluded that organizational justice helps in reduce negative behaviors within the workplace because of its clear impact on individuals, and these conclusions have been received A lot of support in some studies that showed that organizational justice helps in reduce the emergence of bullying within the workplace, which explains the importance of research and its role in improving the work environment, working to achieve organizational justice, and establishing organizational (e.g.,Colquitt 2001;Chou, 2009;Walumbwa et al, 2009;Mourssi-Alfash, 2014;Ghosh & Sinha,2014;Wan, 2016;Al-A'wasa, 2018;Alkhadher & Gadelrab, 2016;Ismail, 2020;Malla & Malla, 2022;Knezović & Neimarlija, 2022)…”
Section: Introductionmentioning
confidence: 99%